FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN DAN PENGGUNAAN MOBILE MARKETING (M-MARKETING) (SURVEY PADA MAHASISWA PELANGGAN TELKOMSEL DI UNIVERSITAS BRAWIJAYA) - Dewi Kumalasari, R. Amalina; Fauzi DH, Achmad; Kumadji, Srikandi (FIA UB, 2013)
Mobile phones usually used for personal purposes will certainly bring a certain reaction from their owners if some unauthorized users make use of this medium for commercial purposes. This study was performed to determine factors influencing consumer acceptance and use of mobile marketing by using factors of utility, contextual information, control, sacrifice, and trust. This research also included factors of attitude toward mobile marketing and behavioral intention to use mobile marketing adopted from the theory of TAM (Technology Acceptance Model) and tested their effects on actual use of mobile marketing. An explanatory research applying a quantitative approach was used. Methods of data collection used a questionnaire with a sample of 145 respondents from the students of Brawijaya University that use Telkomsel as their mobile phone provider. Analysis with Structural Equation Model shows that perceived utility, contextual information, perceived control, perceived sacrifice, and perceived beliefs significantly influence the attitude toward mobile marketing. Perception utility does not have significant effect on the behavioral intention to use mobile marketing but has significant effect on actual use of mobile marketing. Attitude toward mobile marketing significantly influence the behavioral intention to use mobile marketing and behavioral intention to use mobile marketing affects the actual use of mobile marketing.Â Â Â